2012
DOI: 10.2118/153898-pa
|View full text |Cite
|
Sign up to set email alerts
|

Design Considerations of Waterflood Conformance Control With Temperature-Triggered, Low-Viscosity Submicron Polymer

Abstract: In waterfloods, the existence of highly conductive thief zones causes poor volumetric sweep efficiency, resulting in early breakthrough and excessive production of water. A conventional strategy of redirecting injection by closing off perforations yields short-term benefits because diversion occurs near the wellbore. As an alternative, temperature-triggered submicron polymers with low viscosity (popping agents), which give an opportunity for conformance control deep in the reservoir, have been introduced in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Unlike PPGs, BrightWater is not intended for use in fractures (Mustoni et al, 2010;Pritchett et al, 2003). Different BrightWater grades are available for systems of different temperatures and/or different desired thermal reaction rates (Garmeh et al, 2011;Husband et al, 2010;Izgec and Shook, 2012;Ohms et al, 2009;Yanez et al, 2007). Activation/ triggering temperature of the BrightWater particles depends on the crosslinker selected and its associated mechanism of decrosslinking for swelling (Chang et al, 2002;Frampton et al, 2004).…”
Section: Temperature-sensitive Microgelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike PPGs, BrightWater is not intended for use in fractures (Mustoni et al, 2010;Pritchett et al, 2003). Different BrightWater grades are available for systems of different temperatures and/or different desired thermal reaction rates (Garmeh et al, 2011;Husband et al, 2010;Izgec and Shook, 2012;Ohms et al, 2009;Yanez et al, 2007). Activation/ triggering temperature of the BrightWater particles depends on the crosslinker selected and its associated mechanism of decrosslinking for swelling (Chang et al, 2002;Frampton et al, 2004).…”
Section: Temperature-sensitive Microgelsmentioning
confidence: 99%
“…BrightWater has also been used in the Salema field in Brazil (Roussennac and Toschi, 2010) and in the El Borma field in Tunisia (Ghaddab et al, 2010). Garmeh et al (2011) and Izgec and Shook (2012) are useful references for those considering BrightWater technology. Garmeh et al (2011) present a workflow for BrightWater treatment design and evaluation, and also discuss different simulation approaches to evaluate the effects of treatment concentration, slug size, permeability contrast, k v /k h , mobility ratio, and gel activation location.…”
Section: Temperature-sensitive Microgelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effects of TAP adsorption was also evaluated through detailed sensitivity analysis during the simulation study conducted as part of Ebano pilot design. TAP pilot design in Ebano was supported by detailed numerical simulation studies following simulation approaches reported by Garmeh et al (2012) and, Izgec and Shook (2012). The first step was to confirm that the available and history matched black oil model represented the observed water injection profile (PLT at 6,000 bbl/d) before its conversion to compositional/thermal model.…”
Section: Basic Selection Criteria Ebano Fieldmentioning
confidence: 99%